PENINGKATAN KETERAMPILAN MENULIS MELALUI MODEL PEMBELAJARAN TEMATIK KELAS IVB SD NEGERI 24 PONTIANAK TENGGARA - Imanuddin, Muhammad; Halidjah, Siti; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractA common problem in this study is whether using thematic learning models can improve writing learning through thematic learning models in class IVB Southeast Pontianak Elementary School 24? The general objective of this study was to obtain information and describe learning to improve writing learning using thematic learning models in class IVB of 24 Public Elementary Schools in Southeast Pontianak. This research uses descriptive method with the form of classroom action research, and collaborative nature research. The setting in the 24th Elementary School of Public Elementary School in Pontianak with the research subject of fourth grade students supporting 22 people. Techniques using data used are interviews,Observation, measurement with a data collection tool, namely the observation sheet. The collected data is analyzed with the average calculation. This research was conducted in two cycles. In the first cycle the average score of students is 70.45. in the second cycle the average score of students was 79.68, increasing by 9.23. With the use of thematic learning models on Indonesian language learning can improve writing learning, so that it can be concluded that thematic learning learning models can be used to improve the learning skills of class IVB students of Public Elementary School 24 Pontianak Southeast.Â Keywords: Improvement, Writing Skills, with Thematic Models